New species of Myolepta Newman, 1838 (Diptera, Syrphidae) from the Indomalayan Realm - Mengual, Ximo (European Journal of Taxonomy, 2022)
Three new species of Myolepta Newman, 1838 are described from Thailand (M. iota sp. nov.), Laos (M. diaphora sp. nov.) and Indonesia (M. geras sp. nov. from Java), and new records of Myolepta petiolata Thompson, 1971 from Thailand are also provided. Diagnoses, illustrations and known distributional data are given. In addition, the generic affinities and subdivision of Myolepta are discussed based on these newly described taxa.